Bamboo-Inspired bionic microfluidic Reactor: Construction and application for industrial Biocatalysis - Quan Zhou; Litao Wang; Zijing Zhao; Xi Lin; Jiandong Wang; Guosheng Liu; Zihui Cai; Chaobo Huang; Yujie Fu (Bioresource Technology, 2026)

In vitro regeneration of Lily bulblets and artificial seeds development - Zhengjing Wu; Yuan Long; Luping Cui; Mengting Ma; Xun Liu; Zijing Lin; XinYi Wu; Yifang Su (Journal of Plant Biochemistry and Biotechnology, 2026)

Clostridium butyricum Promotes Bone Remodeling by Activating Inflammatory Genes in Mice - Yanxin Jia; Longfei Xu; Zijing Ju; Mengze Song; Yonghao Zhou; Bin Li; Fang Wang; Hai Lin; Shuhong Sun; Haifang Li (Probiotics and Antimicrobial Proteins, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

A three-dimensional reduced-order analysis method for flow and heat transfer performance of PCHE based on Bayesian optimization GPR model - Haowei Lin; Ziyan Zhao; Congyi Wen; Wei Li; Zijing Liu; Pengcheng Zhao (Annals of Nuclear Energy, 2026)

Comparative pharmacokinetics of sixteen components following oral administration of raw and processed Viticis Fructus in rats - Zijing Zhang; Kaili Zhang; Wenwen Li; Zhenguo Lv; Lu Chen; Jinyue Ma; Wenhan Lin; Yameng Zhu; Huizi Ouyang; Jun He (Natural Product Research, 2026)

Forecasting of large-scale tea anthracnose in mountainous region of China though integration of multi-source habitat information with spatiotemporal phenological corrections - Yujuan Huang; Huiqin Ma; Cong Xu; Lin Yuan; Jingfeng Huang; Zijing Jin; Jingcheng Zhang (European Journal of Agronomy, 2026)

Benzofuran-based covalent organic framework with regular fiber-rod structure for efficient photocatalytic H2O2 production under broad visible light - Ting Xu; Zhongxing Zhang; Zijing Wang; Yihao Zhang; Yayang Wang; Yaowen Wang; Liguang Lin; Ping Xue; Jiming Huang; Mi Tang; Lingjun Kong; Xiangcheng Li; et al. (Chemical Engineering Journal, 2026)

Core function and mechanism of electrospun carbon nanofiber aerogels/CNTs for accelerating electron transfer efficiency in microbial fuel cell - Xiaoqiu Lin; Zijing Su; Yuanhao Geng; Ling Wang; Zhiling Li; Haoxu Liu; Congju Li (Journal of Environmental Chemical Engineering, 2025)

Establishment of in vitro grafting system for Tree Peony - Bingjie An; Shuangshuang Yang; Yimiao Sun; Xinrong Fu; Zijing Lin; Wen Gao; Zhengjing Wu (South African Journal of Botany, 2025)

Exploring the direct influence of growth hormone on adamantinomatous craniopharyngioma cells - Zhiwei Xiong; Kai Li; Milai Yu; Zijing Wang; Yihan Wang; Rongjun Chen; Weizhao Li; Keying Zhang; Yucong Lin; Zhixuan Zhang; Haochuan Meng; Guowu Pu; et al. (Tissue and Cell, 2025)

Ambient drying fabrication of mechanically robust, flame-retardant, thermal-insulating cellulose/aramid nanofiber composite foam via freeze-casting combined ion cross-linking - Zijing Liu; Xu Lin; Xueyan Mai; Jiandong Zhuang; Fei Guo; Rilong Yang; Yan Yu; Xuexia Zhang (Carbohydrate Polymers, 2025)

Integrative analysis of the ABC gene family in sorghum revealed SbABCB11 participating in translocation of cadmium from roots to shoots - Bo Zhang; Weitao Jia; Kangqi Lin; Sulian Lv; Zijing Guo; Wenzhu Xie; Yingjiao He; Yinxin Li (Planta, 2025)

Early-life exposure to outdoor temperature and the risk of childhood allergic diseases: A multicentre retrospective cohort study - Faming Wang; Lin Wang; Ying Jiang; Mengju Lan; Wenhui Yang; Zijing Liu; Chan Lu (Building and Environment, 2025)

Soil microbial influences over coexistence potential in multispecies plant communities in a subtropical forest - Weitao Wang; Hangyu Wu; Tingting Wu; Zijing Luo; Wei Lin; Hanlun Liu; Junli Xiao; Wenqi Luo; Yuanzhi Li; Youshi Wang; Chuliang Song; Gaurav Kandlikar; et al. (Ecology, 2024)
Soil microbes have long been recognized to substantially affect the coexistence of pairwise plant species across terrestrial ecosystems. However, projecting their impacts on the coexistence of multispecies plant systems remains a pressing challenge. To address this challenge, we conducted a greenhouse experiment with 540 seedlings of five tree species in a subtropical forest in China and evaluated microbial effects on multispecies coexistence using the structural method, which quantifies how the structure of species interactions influences the likelihood for multiple species to persist. Specifically, we grew seedlings alone or with competitors in different microbial contexts and fitted individual biomass to a population dynamic model to calculate intra‐ and interspecific interaction strength with and without soil microbes. We then used these interaction structures to calculate two metrics of multispecies coexistence, structural niche differences (which promote coexistence) and structural fitness differences (which drive exclusion), for all possible communities comprising two to five plant species. We found that soil microbes generally increased both the structural niche and fitness differences across all communities, with a much stronger effect on structural fitness differences. A further examination of functional traits between plant species pairs found that trait differences are stronger predictors of structural niche differences than of structural fitness differences, and that soil microbes have the potential to change trait‐mediated plant interactions. Our findings underscore that soil microbes strongly influence the coexistence of multispecies plant systems, and also add to the experimental evidence that the influence is more on fitness differences rather than on niche differences.

pH and redox dual-responsive ZIF-8-based nanoplatform for targeted pathogens and environmental protection - Shuhui Hu; Lin-Lin Yang; Chang Yan; Yanan Xiao; Zijing Jin; Xiuhai Gan; Bo Zhang; Wenneng Wu (Chemical Engineering Journal, 2024)

Pollution characteristics and source apportionment of heavy metal(loid)s in soil and groundwater of a retired industrial park - Zijing Xiang; Shijin Wu; Lizhong Zhu; Kun Yang; Daohui Lin (Journal of Environmental Sciences, 2024)

SbYS1 and SbWRKY72 regulate Cd tolerance and accumulation in sweet sorghum - Weitao Jia; Zijing Guo; Sulian Lv; Kangqi Lin; Yinxin Li (Planta, 2024)

Protein extraction from chlorella pyrenoidosa microalgae: Green methodologies, functional assessment, and waste stream valorization for bioenergy production - Zijing Wang; Wangfang Ye; Yijing Wu; Xiaoyu Lin; Cuirong Luan; Xiaowei Xie; Yue Peng; Xiaohong Sun; Chuangyang Shi; Yuancai Lv; Jianlin Shen; Tess Astatkie; et al. (Bioresource Technology, 2024)

Advancing hydrochar production and application: A critical examination of microwave irradiation and blended feedstocks synergy - Shaorong Du; Quan Zhang; Wangfang Ye; Zijing Wang; Zilin Liu; Jianhui Huang; Xin Xu; Yijing Wu; Xiaoyu Lin; Quan Sophia He; Sonil Nanda; Rahil Changotra; et al. (Journal of Cleaner Production, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

Anaerobic membrane bioreactor for the treatment of high-strength waste/wastewater: A critical review and update - Zijing An; Junjie Zhu; Min Zhang; Yan Zhou; Xiaomei Su; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

A novel strategy for enhancing bioremediation of polychlorinated biphenyl-contaminated soil with resuscitation promoting factor and resuscitated strain - Xinru Zhou; Shusheng Zhang; Rui Wang; Zijing An; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Journal of Hazardous Materials, 2023)

Targeting erythrocyte-mediated hypoxia to alleviate lung injury induced by pyrrolizidine alkaloids - Zijing Song; Wei Lian; Yisheng He; Chunyuan Zhang; Ge Lin (Archives of Toxicology, 2023)

Pinocembrin Inhibits P2X4 Receptor–Mediated Pyroptosis in Hippocampus to Alleviate the Behaviours of Chronic Pain and Depression Comorbidity in Rats - Runan Yang; Jingjian Yang; Zijing Li; Ruichen Su; Lifang Zou; Lin Li; Xiumei Xu; Guilin Li; Shuangmei Liu; Shangdong Liang; Changshui Xu (Molecular Neurobiology, 2022)

Comparative analysis of sRNAs, degradome and transcriptomics in sweet sorghum reveals the regulatory roles of miRNAs in Cd accumulation and tolerance - Weitao Jia; Kangqi Lin; Tengxue Lou; Juanjuan Feng; Sulian Lv; Ping Jiang; Ze Yi; Xuan Zhang; Duoliya Wang; Zijing Guo; Yetao Tang; Rongliang Qiu; et al. (Planta, 2021)

The role of formation of pyrrole–ATP synthase subunit beta adduct in pyrrolizidine alkaloid-induced hepatotoxicity - Yao Lu; Jiang Ma; Zijing Song; Yang Ye; Peter P. Fu; Ge Lin (Archives of Toxicology, 2018)